Comparative Effectiveness of Etanercept and Adalimumab in Patient Reported Outcomes and Injection-Related Tolerability. - Iris Navarro-Millán; Lisa J Herrinton; Lang Chen; Leslie Harrold; Liyan Liu; Jeffrey R Curtis (PLoS ONE, 2016)
To describe patient preferences in selecting specific biologics and compare clinical response using patient reported outcomes (PROs) among patients with rheumatoid arthritis (RA) started on different anti-tumor necrosis factor (TNF) therapies.Participants were enrollees in Kaiser Permanente Northern California. Patients with RA who had at least two provider visits and started a new anti-TNF therapy from 10/2010-8/2011, were eligible for participation in this longitudinal study. Using a telephone survey, patient preferences in biologic selection and RAPID3, MDHAQ, and SF-12 scores were collected at baseline and at 6 months. Patient scores rating injection/infusion-site burning and stinging (ISBS) were collected at 6 months.In all, 267 patients with RA responded to the baseline survey, of whom 57% preferred an injectable biologic, 22% preferred an infused biologic, and 21% had no preference. Motivation for injectable biologics was convenience (92%) and for infusion therapy was dislike or lack of self-efficacy for self-injection (16%). After 6 months of treatment with anti-TNF, 70% of the 177 patients who answered the ISBS question reported ISBS with the last dose; on a scale of 1 (none) to 10 (worst), 41% of these reported a score of 2-5; and 29% reported a score of 6-10. Adalimumab users experienced 3.2 times (95% confidence interval 1.2-8.6) the level of ISBS that etanercept users experienced. There were no significant differences in RAPID3, MDHAQ, or SF-12 scores between etanercept or adalimumab initiators.Convenience and fear of self-injection were important considerations to patients selecting a biologic drug. Although more convenient, adalimumab associated with more ISBS than did etanercept, and this rate was higher than reported in clinical trials. At 6 months, PROs did not differ between etanercept and adalimumab users.